2013
DOI: 10.4321/s1135-57272013000100004
|View full text |Cite
|
Sign up to set email alerts
|

Coste de la diarrea asociada a Clostridium difficile en España

Abstract: RESUMENFundamentos: No se dispone de estudios adecuados del coste de las diarreas asociadas a Clostridium difficile (DACD) en España. El objetivo del estudio es estimar el coste de las DACD para el Sistema Nacional de Salud (SNS). Métodos:Se realizó un modelo económico para calcular el coste por episodio de DACD (por antibióticos, prolongación del ingreso hospitalario, procedimientos quirúrgicos, medidas de control de la infección, recurrencias de las infecciones tratadas) y el coste anual de la DACD. El uso d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 9 publications
1
19
0
4
Order By: Relevance
“…According to the authors of this study, the maximum extended stay value used in the model is clinically plausible according to their experience. This assumption was conservative, since the alternative would have been to take the value of 27.3 days from the previous Spanish study [12] or the maximum value observed in England (32.42 days) [23]. However, as this is the most critical variable of the analysis (we must clarify that it is the same for both treatments), it was explored further in the deterministic and probabilistic sensitivity analyses.…”
Section: Discussionmentioning
confidence: 98%
See 4 more Smart Citations
“…According to the authors of this study, the maximum extended stay value used in the model is clinically plausible according to their experience. This assumption was conservative, since the alternative would have been to take the value of 27.3 days from the previous Spanish study [12] or the maximum value observed in England (32.42 days) [23]. However, as this is the most critical variable of the analysis (we must clarify that it is the same for both treatments), it was explored further in the deterministic and probabilistic sensitivity analyses.…”
Section: Discussionmentioning
confidence: 98%
“…In the absence of Spanish data on the maximum value of the extended stay attributable to CDI, it was necessary to make an estimate based on the experience of the Spanish panel of clinical experts. According to a study on CDI cost in Spain [12], the extended stay due to CDI can be up to 27.3 days when recurrences or outbreaks occur. In this regard, the expert panel decided to take a value of 26 days.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations